Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 4 - Proportions, Percents, and Solving Inequalities - Chapters 1-4 Cumulative Review Problem Set - Page 186: 14



Work Step by Step

Using the distributive property and combining like terms, the given expression simplifies to: $5(n+3)-(n+4)-n$ =$5n+15-n-4-n$ =$5n-n-n-4+15$ =$3n+11$ We then substitute $n=7$ in the expression and simplify: $3n+11$ =$3(7)+11$ =$21+11$ =$32$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.